Indium-phosphorus-nitrogen-bismuth material, preparation method thereof, laser and detector using indium-phosphorus-nitrogen-bismuth material, and preparation method for laser and detector - LIANG DAN; WANG SHUMIN; ZHANG LI (2018)
The invention relates to the field of materials science, especially the indium-phosphorus-nitrogen-bismuth material, a preparation method thereof, a laser and a detector using the indium-phosphorus-nitrogen-bismuth material, and a preparation method for the laser and the detector. The indium-phosphorus-nitrogen-bismuth material comprises an indium phosphide substrate; an indium phosphide bufferinglayer which is disposed on the indium phosphide substrate; and an indium-phosphorus-nitrogen-bismuth body which is disposed on the indium phosphide buffering layer. The chemical formula of the indium-phosphorus-nitrogen-bismuth body is InP<1-x-y>NBi, wherein x and y are the concentration percentages of N atoms and bismuth atoms, 0<x<11.1%, and 0<y<11.1%. The indium-phosphorus-nitrogen-bismuth material provided by the invention is smaller in energy gap width, is easier to grow and is more stable. 本发明涉及材料学领域，特别是种铟磷氮铋材料及其制备方法和使用该材料的激光器和探测器及其制备方法，所述铟磷氮铋材料包括：磷化铟衬底；磷化铟缓冲层，设置在所述磷化铟衬底之上；及铟磷氮铋本体，设置在所述磷化铟缓冲层之上；所述铟磷氮铋本体的化学式为InP